2022
DOI: 10.1177/00238309221108647
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Categorical Judgment of L2 Stops: A Link to Proficiency and Acoustic Cue-Weighting

Abstract: This study investigated individual differences in Korean adult learners’ categorical perception of L2 English stops with an aim to explore the relationship of gradient categorizations to perceptual sensitivity to acoustic cues and L2 proficiency. Korean young adult L2 learners of English ( N = 49) participated in two speech perception tasks (visual analog scaling and forced-choice identification) in which they listened to English voiced and voiceless stops and Korean lax and aspirated stops with Voice Onset Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Although our preregistered analyses revealed a somewhat surprising lack of evidence for a relationship between native and nonnative perception, similar findings have been reported in the past. For instance, other work has found that gradiency of native perception on a VAS task did not relate to nonnative discrimination ability (Fuhrmeister et al, 2023) or to scores on a standardized nonnative proficiency task (Kong & Kang, 2022). It may be that native gradiency does not relate strongly to nonnative outcomes due to differences in some of the processing strategies involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although our preregistered analyses revealed a somewhat surprising lack of evidence for a relationship between native and nonnative perception, similar findings have been reported in the past. For instance, other work has found that gradiency of native perception on a VAS task did not relate to nonnative discrimination ability (Fuhrmeister et al, 2023) or to scores on a standardized nonnative proficiency task (Kong & Kang, 2022). It may be that native gradiency does not relate strongly to nonnative outcomes due to differences in some of the processing strategies involved.…”
Section: Discussionmentioning
confidence: 99%
“…Gradiency (as measured by VAS tasks) appears to be a relatively consistent property of the individual. It has been shown to be related across different testing sessions using the same stimuli (Kong & Edwards, 2016), across different contrasts (Fuhrmeister & Myers, 2021; Kapnoula & McMurray, 2021; but see Kapnoula et al, 2021 for contrasting evidence), and across native and nonnative perception (Kong & Kang, 2022). Individual differences in gradiency may reflect anatomical differences in auditory processing architecture, since they relate to differences in cortical surface area (Fuhrmeister & Myers, 2021) and in how cues are neurally encoded and transformed along the auditory pathway (Kapnoula & McMurray, 2021; Ou & Yu, 2022).…”
Section: Individual Differences In Native Speech Perceptionmentioning
confidence: 99%
See 2 more Smart Citations